THE ROLE OF RELIGIOUS STUDY GROUPS IN FOSTERING ANTI-CORRUPTION BEHAVIOR AND ITS IMPLICATIONS FOR LOCAL DEMOCRATIC PRACTICES IN METRO CITY - Nadirsah Hawari; Agustam Agustam; Muntaha Artalim (Akademika : Jurnal Pemikiran Islam, 2023)
This study discusses the efforts of majlis taklim management to instill a clean-living attitude and behavior in combating corrupt practices during political years, including local contests such as regional elections. Furthermore, it is considered important because the majlis taklim congregation consists of individuals constantly nurtured mentally and spiritually through long and regular periods of guidance. In the context of Metro City, there are suspicions of a high prevalence of pragmatic political behavior during campaigns. Therefore, the central concern revolves around the clarity of the role and roadmap of a majlis taklim managed by the DKM (mosque management board) in promoting sound political morality and its potential to diminish the prevalence of money politics during regional elections. This study takes the form of a qualitative and descriptive analysis approach, using interviews and questionnaires as the main data sources distributed to the managers and congregation members. The findings indicate that the majlis taklim in Metro City has regular studies cultivating social morality during elections. However, these initiatives are not yet integrated into a standardized printed curriculum that can serve as a comprehensive reference. A majlis taklim congregation is a group of people who are not easily swayed by money politics during regional elections but some members are still inclined towards such practices.